The effects of urban land use gradients on wild bee microbiomes - Nguyen, Phuong N.; Rehan, Sandra M. (Frontiers in Microbiology, 2022)
Bees and their microbes interact in complex networks in which bees form symbiotic relationships with their bacteria and fungi. Research has shown that microbial composition and abundance affect bee health through nutrition, immunity, and fitness. In ever-expanding urban landscapes, land use development changes bee habitats and floral resource availability, thus altering the sources of microbes that wild bees need to establish their microbiome. Here, we implement metabarcoding of the bacterial 16S and fungal ITS regions to characterize the diversity and composition of the microbiome in 58 small carpenter bees, Ceratina calcarata, across urban land use gradients (study area 6425 km2). By categorizing land use development, green space, precipitation, and temperature variables as indicators of habitat across the city, we found that land use variables can predict microbial diversity. Microbial composition was also found to vary across urban land use gradients, with certain microbes such as Acinetobacter and Apilactobacillus overrepresented in less urban locations and Penicillium more abundant in developed areas. Environmental features may also lead to differences in microbe interactions, as co-occurrences between bacteria and fungi varied across percent land use development, exemplified by the correlation between Methylobacterium and Sphingomonas being more prevalent in areas of higher urban development. Surrounding landscapes change the microbial landscape in wild bees and alter the relationships they have with their microbiome. As such, urban centres should consider the impact of growing cities on their pollinators’ health and protect wild bees from the effects of anthropogenic activities.